Longitudinal analysis of genetic and epigenetic changes in human pluripotent stem cells in the landscape of culture-induced abnormality - Kim, Yun Jeong; Kang, Byunghee; Kweon, Solbi; Oh, Sejin; Kim, Dayeon; Gil, Dayeon; Lee, Hyeonji; Kim, Jung Hyun; Ju, Ji Hyeon; Roh, Tae Young; Hong, Chang Pyo; Cha, Hyuk Jin (Experimental and Molecular Medicine, 2024)
Human embryonic stem cells (hESCs) are naturally equipped to maintain genome integrity to minimize genetic mutations during early embryo development. However, genetic aberration risks and subsequent cellular changes in hESCs during in vitro culture pose a significant threat to stem cell therapy. While a few studies have reported specific somatic mutations and copy number variations (CNVs), the molecular mechanisms underlying the acquisition of ‘culture-adapted phenotypes’ by hESCs are largely unknown. Therefore, we conducted comprehensive genomic, single-cell transcriptomic, and single-cell ATAC-seq analyses of an isogenic hESC model displaying definitive ‘culture-adapted phenotypes’. We found that hESCs lacking TP53, in which loss-of-function mutations were identified in human pluripotent stem cells (hPSCs), presented a surge in somatic mutations. Notably, hPSCs with a copy number gain of 20q11.21 during early passage did not present ‘culture-adapted phenotypes’ or BCL2L1 induction. Single-cell RNA-seq and ATAC-seq analyses revealed active transcriptional regulation at the 20q11.21 locus. Furthermore, the induction of BCL2L1 and TPX2 to trigger ‘culture-adapted phenotypes’ was associated with epigenetic changes facilitating TEA domain (TEAD) binding. These results suggest that 20q11.21 copy number gain and additional epigenetic changes are necessary for expressing ‘culture-adapted phenotypes’ by activating gene transcription at this specific locus.
Keywords: bcl-X Protein; Cell Differentiation; Cell Line; DNA Copy Number Variations; Epigenesis, Genetic; Human Embryonic Stem Cells; Humans; Mutation; Phenotype; Pluripotent Stem Cells; Single-Cell Analysis; Transcriptome; Tumor Suppressor Protein p53